Constructing a Christ-centred identity: A social identity reading of the Epistle to Titus - Momberg, Rudolph P.; Kok, Jacobus (Hervormde teologiese studies, 2025)
The Pastoral Epistle to Titus offers both theological insights and practical guidance for Christ-followers on the island of Crete, a context moulded by enduring public reputations and persistent negative cultural stereotypes. This article applies the Social Identity Theory (SIT) to explore how the letter to Titus intends to transform the Cretan identity through comparative fit, normative fit, salience and theological dispositions. A social-rhetorical analysis demonstrates how the epistle to Titus redefines social structures by transferring the emphasis on social categories to divine χάρις. The text challenges personal self-esteem and external prejudice by emphasising virtues that contrast the dominant vices and present a Christ-centred identity that challenges the Cretan negative prototypicality and discrimination. This article argues that the epistle to Titus presents a purposeful strategy to reconstruct the social identity within a culturally contested context. Contribution: The contribution to scholarship lies in the integration of theological analysis with SIT, providing new insights into the dynamics of early Christ-following identity formation.